Proceedings of the 5th International Seminar of Public Health and Education, ISPHE 2020, 22 July 2020, Universitas Negeri Semar 2020
DOI: 10.4108/eai.22-7-2020.2300320
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cardio and Tabata Exercises on Decreasing Body Fat, Weight and Increasing Physical Fitness

Abstract: The purpose of this study is to analyze the effects of cardio exercise and tabata method on body weight, body fat, and physical fitness. This study applied experimental design with pretest and posttest. A total of 27 respondents were all males and had BMI over 25.0 (overweight and obese). They were then divided into 3 groups: control (K1), cardio group (K2) and Tabata group (K3), each consisting of 9 individuals. K1 did not receive any intervention. While K2 and K3 were received six-weeks interventions, three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Such as the study of [41], it was reported that a 12week HIIT is significantly effective for obese adults. Similarly with the findings of [54], observed that TABATA method represents an effective way in reducing body weight and fat, most especially to those overweight and obese individuals. However, based on the results of the study, TABATA training program is not highly suggested to introduce, most especially for students that falls under the underweight and slightly normal category as this may cause detrimental issues concerning their health.…”
Section: Discussionsupporting
confidence: 77%
“…Such as the study of [41], it was reported that a 12week HIIT is significantly effective for obese adults. Similarly with the findings of [54], observed that TABATA method represents an effective way in reducing body weight and fat, most especially to those overweight and obese individuals. However, based on the results of the study, TABATA training program is not highly suggested to introduce, most especially for students that falls under the underweight and slightly normal category as this may cause detrimental issues concerning their health.…”
Section: Discussionsupporting
confidence: 77%
“…The catecholamine hormone activates lipolysis by binding to 𝛽-adrenoceptors, decreasing body fat (Valentine et al, 2022). In addition, high-intensity exercise such as Tabata will further increase the secretion of growth hormone, which is believed to increase lipolysis (Taufikkurrachman et al, 2020). Tabata training requires more energy.…”
Section: Comparison Of Cardio and Tabata Training Methods On Fat Perc...mentioning
confidence: 99%
“…Cardio exercises effective for losing fat are 20-60 minutes long with an intensity of 65% -75% of the maximum pulse (Andini et al, 2016). Cardio exercise for more than 45 minutes at low or moderate intensity is common in society and can burn fat and improve cardiovascular health and fitness (Taufikkurrachman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches on effect of Tabata training on adipose tissue were mostly conducted on adolescents [22,23], overweight men [24] and overweight women [25,26]. Some beneficial highlights were made in domain of anaerobic capacity and physical and motoric characteristic of athletes [27,28,29,30].…”
mentioning
confidence: 99%